Studies on Activities and Chemical Characterization of Medicinal Plants in Search for New Antimalarials: A Ten Year Review on Ethnopharmacology - Isabela P. Ceravolo; Anna C. Aguiar; Joseph O. Adebayo; Antoniana U. Krettli (Frontiers Media S.A., 2021)
Malaria is an endemic disease that affected 229 million people and caused 409 thousand deaths, in 2019. Disease control is based on early diagnosis and specific treatment with antimalarial drugs since no effective vaccines are commercially available to prevent the disease. Drug chemotherapy has a strong historical link to the use of traditional plant infusions and other natural products in various cultures. The research based on such knowledge has yielded two drugs in medicine: the alkaloid quinine from Cinchona species, native in the Amazon highland rain forest in South America, and artemisinin from Artemisia annua, a species from the millenary Chinese medicine. The artemisinin-based combination therapies (ACTs), proven to be highly effective against malaria parasites, and considered as "the last bullet to fight drug-resistant malaria parasites," have limited use now due to the emergence of multidrug resistance. In addition, the limited number of therapeutic options makes urgent the development of new antimalarial drugs. This review focuses on the antimalarial activities of 90 plant species obtained from a search using Pubmed database with keywords "antimalarials," "plants" and "natural products." We selected only papers published in the last 10 years (2011-2020), with a further analysis of those which were tested experimentally in malaria infected mice. Most plant species studied were from the African continent, followed by Asia and South America; their antimalarial activities were evaluated against asexual blood parasites, and only one species was evaluated for transmission blocking activity. Only a few compounds isolated from these plants were active and had their mechanisms of action delineated, thereby limiting the contribution of these medicinal plants as sources of novel antimalarial pharmacophores, which are highly necessary for the development of effective drugs. Nevertheless, the search for bioactive compounds remains as a promising strategy for the development of new antimalarials and the validation of traditional treatments against malaria. One species native in South America, Ampelozyzyphus amazonicus, and is largely used against human malaria in Brazil has a prophylactic effect, interfering with the viability of sporozoites in in vitro and in vivo experiments.